Edukasi Psikologis Bagi Ibu Pasca Keguguran (Miskram) Untuk Mencegah Depresi Dan Trauma Kehamilan - Dewi Parwati; Muh. Kardi Rais; Raissa Patrisia; Cakrawati R; Rezqiqah Aulia Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Miscarriage is a traumatic experience that can have physical and psychological effects on mothers. Many mothers who have experienced miscarriage suffer from stress, depression, and even trauma that can affect their next pregnancy. This community service activity aims to provide psychological education to mothers who have experienced miscarriage in order to prevent depression and pregnancy trauma. The activity was carried out by lecturers and students of the Midwifery Study Program at Puskesmas X in August 2025. The activity methods included a pre-test, interactive psychological counseling, relaxation simulation, and a post-test. The results of the activity showed an increase in participants' knowledge from 58.4% (pre-test) to 87.2% (post-test) and a decrease in anxiety levels based on the DASS-21 questionnaire. It can be concluded that psychological education is effective in increasing the knowledge and emotional readiness of mothers after miscarriage, thereby preventing depression and pregnancy trauma.